Improving Product Purity of Ethylene Glycol Production from Ethylene Oxide by Modify Process Using Multi-stage Distillation - Mirza Aufaa Nailendra; Maulana Reand Wijaya; Rafael Christofer Panggabean; Thariq Rifansyah; Yessa Liza Halimah (UPT Laboratorium Terpadu, Universitas Diponegoro, 2026)
Ethylene glycol (EG) is an important industrial chemical widely used in the manufacture of polyester fibers, antifreeze formulations, and heat-transfer fluids. Industrially, EG is produced through the hydration of ethylene oxide; however, achieving high product purity remains a significant challenge due to the presence of water and higher glycols in the reaction mixture. This study proposes a process modification aimed at improving ethylene glycol purity through the implementation of a multi-stage distillation system. The conventional single-stage distillation configuration was evaluated and compared with a modified two-stage distillation scheme. Simulation results indicate that the proposed modification significantly enhances separation performance, increasing ethylene glycol mole fraction from 0.8991 in the unmodified process to 0.9990 in the modified configuration. The improvement is attributed to better distribution of separation duties and enhanced control of vapor–liquid equilibrium across multiple distillation stages. These findings demonstrate that multi-stage distillation, supported by rigorous process simulation, is an effective strategy for producing high-purity ethylene glycol and offers valuable insights for industrial process optimization and design. Copyright © 2026 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).